Journalism - Allan, Stuart (McGraw-Hill Education, 2007)
This edited collection introduces news media studies to the undergraduate reader. Drawing together an exciting selection of original essays from journalism, cultural studies and media studies, this text highlights several of the most significant topics and debates in this field. Journalism is organized to address a series of themes pertinent to the ongoing conceptual development of news media studies around the globe, with a particular focus on work conducted in the United States and Britain. An introductory chapter by the editor sets the scene for the discussion by providing a concise, up-to-
https://katalog.adlr.link/Record/0-72270125X